Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1254/jphs.fp0070475
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Spinal Cholecystokinin and Neurokinin-1 Receptors Is Associated With the Attenuation of Intrathecal Morphine Analgesia Following Electroacupuncture Stimulation in Rats

Abstract: Abstract. We previously demonstrated that electroacupuncture (EA) stimulation both produced antinociception and attenuated intrathecal (i.t.) morphine analgesia, suggesting that EA is capable of inducing two opposing systems, that is, opioid and anti-opioid mechanisms. This study examined the involvement of cholecystokinin (CCK) in the anti-opioid effects following EA in the spinal cord. EA was applied to commonly used acupoints for antinociception, ST-36 located 5-mm lateral to the anterior tubercle of the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
4
10
0
Order By: Relevance
“…A 1.0 ng dose of CCK-8S was used, and CCK-8S or vehicle (0.9% saline) was co-administered with morphine. Consistent with the results of Fukazawa et al (2007) and as observed in our pilot studies, this dose of CCK-8S was a low dose that did not affect the antinociception produced by 3 μg i.t. morphine in naïve rats.…”
Section: Morphine Analgesic Trialssupporting
confidence: 92%
See 1 more Smart Citation
“…A 1.0 ng dose of CCK-8S was used, and CCK-8S or vehicle (0.9% saline) was co-administered with morphine. Consistent with the results of Fukazawa et al (2007) and as observed in our pilot studies, this dose of CCK-8S was a low dose that did not affect the antinociception produced by 3 μg i.t. morphine in naïve rats.…”
Section: Morphine Analgesic Trialssupporting
confidence: 92%
“…administration of CCK-8S attenuated the effects of morphine in animals with carrageenan inflammation (but not in normal animals), the present results show that a low dose of CCK-8S (1 ng) decreases morphine analgesia in LPS-treated rats, but not in naïve rats. Consistent with Fukazawa et al (2007), naïve rats (non-LPS rats) do not show a decrease of morphine sensitivity with this dose of CCK-8S. This suggests that LPS-treated rats show increased responsiveness to the anti-opioid effects i.t.…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, the expression of Cck was significantly increased after 2 Hz EA stimulation and not different between HR and NR in DH. This result that Cck mRNA level was increased after EA and there was no difference between HR and NR was consistent with the previous studies in DH and supraspinal regions [6], [10], [46], while the Cck protein level was higher in NR than HR in the midbrain periaqueductal gray and the perfusate of the rat spinal cord [6], [16]. The mRNA level of the Cck-a receptor in DH had no significant difference in NR and HR of this study, which was inconsistent with one previous study in hypothalamus that Cck-a mRNA level was high expressed in NR than HR [8].…”
Section: Discussionsupporting
confidence: 93%
“…Preclinical data on IT opioids published between January 15, 2007, and March 1, 2011, are summarized in Table 9(14,15,56–80).…”
Section: Supporting Literature Reviewmentioning
confidence: 99%